PENGARUH HALLYU, AMBASSADOR MEREK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ATAS PRODUK REPUBLIK NATUR DI YOGYAKARTA - Ema Sukma Wardani; Awan Santosa (Jurnal Apresiasi Ekonomi, 2020)
ABSTRACTThis study aims to determine the Influence of Hallyu Wave, Brand Ambassador and Brand Image on the Consumer Purchase Decision on Nature Republic Products in Yogyakarta. The researcher conducted this study to Nature Republic consumers who live in Yogyakarta by distributing questionnaires so that the total sample is 100 respondents. The analysis in this study uses multiple linear regression. The results of this study indicate that brand image is the only variable that has a positive and significant influence on consumer purchasing decisions on Nature Republic products in Yogyakarta.